2013
DOI: 10.1016/j.immuni.2012.11.013
|View full text |Cite
|
Sign up to set email alerts
|

The E3-Ligase TRIM Family of Proteins Regulates Signaling Pathways Triggered by Innate Immune Pattern-Recognition Receptors

Abstract: Summary Innate immunity conferred by the type I interferon is critical for antiviral defense. To date only a limited number of tripartite motif (TRIM) proteins has been implicated in modulation of innate immunity and anti-microbial activity. Here we report the cDNA cloning and systematic analysis of all known 75 human TRIMs. We demonstrate that surprisingly roughly half of the 75 TRIM-family members enhanced the innate immune response, and that they do this at multiple levels in signaling pathways. Moreover, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
288
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(319 citation statements)
references
References 32 publications
21
288
0
4
Order By: Relevance
“…Recently, a systematic analysis of all 75 known human TRIMs revealed that nearly half of these TRIMs could enhance the innate immune response. Moreover, mutational analysis demonstrated that all of the six tested TRIMs required an intact RING domain for their activity (30), suggesting that the RING domain may serve as a prevailing machinery for TRIMs. Intriguingly, TRIM14 does not contain an N-terminal RING domain but still potently enhances the innate immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a systematic analysis of all 75 known human TRIMs revealed that nearly half of these TRIMs could enhance the innate immune response. Moreover, mutational analysis demonstrated that all of the six tested TRIMs required an intact RING domain for their activity (30), suggesting that the RING domain may serve as a prevailing machinery for TRIMs. Intriguingly, TRIM14 does not contain an N-terminal RING domain but still potently enhances the innate immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitination is one of the most versatile PTMs and is important for antiviral responses. Many members of the TRIM family can induce K63-or K48-linked ubiquitination [32]. For example, TRIM25 and TRIM56 can induce RIG-I and STING ubiquitination, respectively, by K63-mediated linkage, which are essential for type I IFN production [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the T. adhaerens TRIM has multiple human co-orthologs within paralogons of the MHC, neurotrophin or JN sets, and all of them share the same domain structure (72). Among them are TRIM1 and TRIM9, two key modulators of the IFN pathway that strongly inhibit viral growth (73). In the absence of IFN, an antiviral activity of the T. adhaerens TRIM might proceed via direct binding (and ubiquitination) of viral proteins as for TRIM5 in primates, or via modulation of expression of other antiviral factors.…”
Section: Discussionmentioning
confidence: 99%